2022
DOI: 10.1093/jrr/rrac044
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed patient fixation system using a dedicated mouthpiece and dental impression materials for head and neck radiotherapy: a preliminary study

Abstract: We evaluated the basic characteristics and efficacy of our newly developed patient fixation system for head and neck radiotherapy that uses a dedicated mouthpiece and dental impression materials. The present investigation demonstrated that with this system, the changes in the absorbed dose to water depending on the material of the mouthpiece were small, with a maximum of 0.32% for a 10-MV photon beam. For the dental impression material, we selected a silicone material with the lowest Hounsfield unit (HU) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In 2022, the interfractional head-up and–down motions in the thermoplastic mask with and without 3D printed tongue-positioning devices were investigated using magnetic resonance imaging [ 14 ]. It was revealed that head motions with the tongue-positioning devices decreased significantly compared to the motions without tongue-positioning devices [ 14 ]. In 2021, dosimetric characteristics and setup stability of a patient-specific semi-customized tongue-positioning device were compared with those of a standard mouthpiece.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2022, the interfractional head-up and–down motions in the thermoplastic mask with and without 3D printed tongue-positioning devices were investigated using magnetic resonance imaging [ 14 ]. It was revealed that head motions with the tongue-positioning devices decreased significantly compared to the motions without tongue-positioning devices [ 14 ]. In 2021, dosimetric characteristics and setup stability of a patient-specific semi-customized tongue-positioning device were compared with those of a standard mouthpiece.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, it was reported that the use of positioning stent to reduce the irradiation dose to the palate resulted in a reduction of radiation-induced oral mucositis on the palate [10]. Several three-dimensional (3D) printed customized tongue devices were suggested to take the patient-specific structures into account, and dosimetric efficacies were also reported [6][7][8][9][12][13][14][15][16]. In 2022, the interfractional head-up and-down motions in the thermoplastic mask with and without 3D printed tongue-positioning devices were investigated using magnetic resonance imaging [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation